2018
DOI: 10.1016/j.devcel.2018.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Small RNAs Are Trafficked from the Epididymis to Developing Mammalian Sperm

Abstract: The biogenesis of the RNA payload of mature sperm is of great interest, because RNAs delivered to the zygote at fertilization can affect early development. Here, we tested the hypothesis that small RNAs are trafficked to mammalian sperm during the process of post-testicular maturation in the epididymis. By characterizing small RNA dynamics during germ cell maturation in mice, we confirm and extend prior observations that sperm undergo a dramatic switch in the RNA payload from piRNAs to tRNA fragments (tRFs) up… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
318
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 313 publications
(357 citation statements)
references
References 78 publications
12
318
0
2
Order By: Relevance
“…Temple‐Smith & Bedford, ) and eutherian mammals (e.g. Bedford, ; Baker et al ., ; Sullivan & Saez, ; Aalberts, Stout, & Stoorvogel, ; Skerget et al ., ; Machtinger, Laurent, & Baccarelli, ; Sharma et al ., ; Nixon et al ., ). Although less thoroughly studied, similar changes to sperm may occur within the Wolffian duct of reptiles (e.g.…”
Section: Elements Of the Life History Of Spermmentioning
confidence: 99%
“…Temple‐Smith & Bedford, ) and eutherian mammals (e.g. Bedford, ; Baker et al ., ; Sullivan & Saez, ; Aalberts, Stout, & Stoorvogel, ; Skerget et al ., ; Machtinger, Laurent, & Baccarelli, ; Sharma et al ., ; Nixon et al ., ). Although less thoroughly studied, similar changes to sperm may occur within the Wolffian duct of reptiles (e.g.…”
Section: Elements Of the Life History Of Spermmentioning
confidence: 99%
“…It is gradually revealed that the substantial modifications in the sncRNA content in the spermatozoa is one of the major biological events during their epididymal transit (Nixon et al, 2015b;Chen et al, 2016a;Chu et al, 2017;Sharma et al, 2018). Additionally, the existence of piRNA sequences in the mature spermatozoa in the cauda epididymis is also quite intriguing.…”
Section: Progress Over the Past Decadementioning
confidence: 99%
“…In addition to the complex array of proteins and ions, mounting evidence suggests that the epididymal luminal environment contains different types of sncRNAs which are encapsulated and carried by the extracellular microvesicles known as the epididymosomes (Belleannee et al, 2013a;Sullivan & Saez, 2013;Nixon et al, 2015b). The existence of different sncRNAs, including miRNAs (Belleannee et al, 2013a;Reilly et al, 2016) and tsRNAs (Sharma et al, 2018) in the epididymosomes sheds light on the previously underappreciated function of epididymosome-mediated sperm sncRNA modification, through the mechanism similar to what was described for exosomal trafficking of miRNAs in nematodes, plants (Sarkies & Miska, 2014), and somatic cell contexts (Valadi et al, 2007;Gibbings et al, 2009;Zhang et al, 2015). Apart from the well-known function of facilitating the secretion of proteins that do not have a signal peptide (Cornwall, 2009), the epididymosomes are largely involved the exchange of sncRNAs between the epithelium and the spermatozoa.…”
Section: Progress Over the Past Decadementioning
confidence: 99%
See 2 more Smart Citations